2008
DOI: 10.1093/ageing/afn097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of walking periods and number of steps in older adults and patients with Parkinson's disease: accuracy of a pedometer and an accelerometry-based method

Abstract: The aim of this study was to examine if walking periods and number of steps can accurately be detected by a single small body-fixed device in older adults and patients with Parkinson's disease (PD). Results of an accelerometry-based method (DynaPort MicroMod) and a pedometer (Yamax Digi-Walker SW-200) worn on each hip were evaluated against video observation. Twenty older adults and 32 PD patients walked straight-line trajectories at different speeds, of different lengths and while doing secondary tasks in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 32 publications
7
91
0
Order By: Relevance
“…Overall the methodological quality of the studies examined was high, with each scoring ≥7. Of the assessed studies, 10 included participants with multiple sclerosis [32][33][34][35][36][37][38][39][40][41], 7 included participants after stroke [32,33,[42][43][44][45][46], 4 included participants with PD [27,33,47,48], 3 included participants with a spinal cord injury [32,49,50], 2 included participants with cerebral palsy [51,52], 2 included participants with a traumatic brain injury [32,42], and participants with Rett syndrome [53] and muscular dystrophy [32] were included in 1 study each. The most frequently used monitors included the StepWatch activity monitor (a biaxial accelerometer) [39,41,42,44,53], the ActiGraph GT3X (a triaxial accelerometer) [35,39,40,50], the SWA (a multisensor device) [46,49,52], and the Digi-Walker pedometer [27,32...…”
Section: Table 2 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the methodological quality of the studies examined was high, with each scoring ≥7. Of the assessed studies, 10 included participants with multiple sclerosis [32][33][34][35][36][37][38][39][40][41], 7 included participants after stroke [32,33,[42][43][44][45][46], 4 included participants with PD [27,33,47,48], 3 included participants with a spinal cord injury [32,49,50], 2 included participants with cerebral palsy [51,52], 2 included participants with a traumatic brain injury [32,42], and participants with Rett syndrome [53] and muscular dystrophy [32] were included in 1 study each. The most frequently used monitors included the StepWatch activity monitor (a biaxial accelerometer) [39,41,42,44,53], the ActiGraph GT3X (a triaxial accelerometer) [35,39,40,50], the SWA (a multisensor device) [46,49,52], and the Digi-Walker pedometer [27,32...…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…The validity and reliability of activity monitoring in other populations may not translate easily to individuals with neurological diseases, as activity monitoring in individuals with neurological diseases may be complicated by a wide range of neurological impairments such as gait abnormalities [22], weakness [23], spasticity [24], or tremor [25]. For example, it has been demonstrated that gait parameters such as speed and distance can be accurately estimated using a triaxial accelerometer device in healthy adults [26], but the accuracy is not as high in individuals with PD while using the same device [27]. Therefore it is important to explore the validity and reliability of activity monitors in this population before these monitors can be widely implemented in clinical trials and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the activity of older women may in fact be underestimated in community-dwelling elderly [17]. Women tend to be more involved in household tasks than men and these tasks are sometimes accompanied by 'shuffling steps' rather than actual steps; pedometers are not as effective as triaxial accelerometers in measuring these shuffling steps [42]. Therefore, physical activity in elderly women might be underestimated in community studies, leading to the conclusion that older men are physically more active whereas women are in fact just as active or even more active, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been reported that a triaxial accelerometer would be better suited than a pedometer to count shuffling steps and slow speed, such as patients with Parkinson's disease (Dijkstra et al, 2008) and, furthermore, that a piezoelectric sensor can accurately calculate the number of steps taken by an individual at slow speed (Melanson et al, 2004). The triaxial accelerometer (piezo-type) was used in the present study, and it was confirmed that this accelerometer could calculate the number of steps when subjects were walking at 0.4-0.5 m/s in our pilot study (not reported).…”
Section: Daily Ambulatory Activitymentioning
confidence: 99%